An empirical research on the Initial Public Offer Market in Singapore - Toh, Chee Kiong (2014)
The focus of this research is to determine whether profitable investments can be made by subscribing the IPOS underwritten by a particular underwriter group. Two categories of underwriters have been singled out, mainly DBS Bank and Non-DBS institutions.